2016
DOI: 10.1111/bjd.14946
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal skin barrier

Abstract: Linked Article: Chittock et al. Br J Dermatol 2016; 175:713–20.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Diffuse reflectance spectroscopy (DRS) has been used for a number of biomedical applications including epithelial tissue characterization, brain study, breast cancer detection and surgical margin assessment, skin pigmentation research etc. [20][21][22][23][24][25][26][27][28] DRS has been preferred technique for its application in blood perfusion and tissue oxygenation studies within ultraviolet-visible wavelength range and researchers have extended these spectroscopic measurements range up to NIR (400-1600 nm) to include absorption from lipid and water chromophores. [29,30] It has been reported that extended NIR wavelength region measurement renders a better discrimination between benign and tumor sites as well as accurate estimation of chromophores present in the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse reflectance spectroscopy (DRS) has been used for a number of biomedical applications including epithelial tissue characterization, brain study, breast cancer detection and surgical margin assessment, skin pigmentation research etc. [20][21][22][23][24][25][26][27][28] DRS has been preferred technique for its application in blood perfusion and tissue oxygenation studies within ultraviolet-visible wavelength range and researchers have extended these spectroscopic measurements range up to NIR (400-1600 nm) to include absorption from lipid and water chromophores. [29,30] It has been reported that extended NIR wavelength region measurement renders a better discrimination between benign and tumor sites as well as accurate estimation of chromophores present in the tissue.…”
Section: Introductionmentioning
confidence: 99%